2018
DOI: 10.1017/s1047951118000379
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of disseminated adenovirus infection with cidofovir and intravenous immunoglobulin in an infant following heart transplant

Abstract: For most patients, adenoviruses cause few acute health concerns and are often self-limiting. Patients who are immunocompromised or immunosuppressed, however, are at risk for disseminated adenovirus and suffer high morbidity and mortality, without well-defined treatment options. We report the case of a 9-month-old boy who was successfully treated for disseminated adenovirus infection with intravenous immunoglobulin and cidofovir 3 months post heart transplant, tailored to serum adenoviral load and clinical resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…The incidence of AdV infections among SOT recipients is 5 to 22%, usually within the first 6 months posttransplantation. 4 8 79 145 200 201 202 Adenovirus infections have been noted in recipients of intestinal, 203 204 liver, 205 206 207 208 kidney, 119 123 128 209 210 211 heart, 200 212 213 214 and lung 215 216 transplants. Among SOT recipients, risk factors for AdV include pediatric age, 4 79 208 217 donor-positive/recipient-negative AdV status, 79 and receipt of antilymphocyte antibodies.…”
Section: Specific Patient Populations At Riskmentioning
confidence: 99%
“…The incidence of AdV infections among SOT recipients is 5 to 22%, usually within the first 6 months posttransplantation. 4 8 79 145 200 201 202 Adenovirus infections have been noted in recipients of intestinal, 203 204 liver, 205 206 207 208 kidney, 119 123 128 209 210 211 heart, 200 212 213 214 and lung 215 216 transplants. Among SOT recipients, risk factors for AdV include pediatric age, 4 79 208 217 donor-positive/recipient-negative AdV status, 79 and receipt of antilymphocyte antibodies.…”
Section: Specific Patient Populations At Riskmentioning
confidence: 99%
“…To date, it has been reported that ribavirin and cidofovir treatment [41][42][43][44] and adoptive transfer of Ad-specific T cells [45,46] effectively prevented Ad infections in patients following transplantation. Intravenous immunoglobulin (IVIG) has been used to treat severe Ad infection in combination with ribavirin and cidofovir [47][48][49], but the therapeutic effects of IVIG itself are unclear [50]. Our results suggest that the effect of IVIG is attenuated by progeny Ad in the presence of nAb and that inhibition of this infection is an attractive strategy for patients treated with IVIG.…”
Section: Discussionmentioning
confidence: 84%
“…Specific T cell response correlates with viral clearance [ 1 ]. Infusion of intravenous immunoglobulin is routinely recommended in immunocompromised patients, considering the potential of containing high levels of neutralising antibodies against lower adenoviral serotypes [ 24 ], commonly co-administered with other therapeutic approaches [ 25 ]. Tapering immunosuppression is desirable, but is not always an option.…”
Section: Discussionmentioning
confidence: 99%